Non‐Ablative 1927 nm Fractional Thulium Fiber Laser: New, Promising Treatment Modality for Riehl's Melanosis. Issue 5 (1st December 2020) - Kim, Su Min; Hwang, Shinwon; Almurayshid, Abdurrahman; Park, Min‐Young; Oh, Sang Ho
Abstract : Background and Objectives: The treatment of Riehl's melanosis, also known as pigmented contact dermatitis, is highly challenging. Intense pulsed light (IPL) and 1064 nm Q‐switched Nd:Yag (QS‐Nd:YAG) laser are reported to have some efficacy. However, no single effective treatment has yet been identified. In this study, we demonstrated the efficacy and safety of the non‐ablative 1927 nm fractional thulium fiber laser (TFL, LASEMD™; Lutronic Corp., Goyang, Korea) for patients with Riehl's melanosis. Study Design/Materials and Methods: A retrospective chart and photographic review of nine patients with Riehl's melanosis, who had received at least three sessions of TFL treatment, was performed. Before the start of TFL treatment, combination treatment with a topical cream containing hydroquinone, low‐fluence QS‐Nd:YAG laser, pulsed dye laser, and IPL was used with variable and discouraging effects. Seven patients were treated on the face and two patients on the neck with three to seven sessions at 1‐month intervals. Clinical improvement was assessed using clinical photos taken before and after every treatment session according to dermal pigmentation area and severity index (DPASI) and a quartile grading scale by two blinded dermatologists. Results: Patients underwent three to seven sessions of TFL treatment depending on severity of pigmentation. Of nine patients, six demonstrated a clinical improvement of 51%–75%, one demonstrated an improvement of 76%–100%, and two showed an improvement of 26%–50% after treatment. The DPASI was significantly decreased from 9.55 to 5.25 on average. Melanin index was decreased after treatment in two patients whose melanin index were measured at initial visits. Treatment‐related adverse events, such as scarring or postinflammatory hyperpigmentation (PIH), were not observed in all patients except for transient erythema and swelling. Conclusions: This report suggests that TFL could be an alternative and/or additive treatment option for hyperpigmentation in intractable Riehl's melanosis and might be a promising treatment for PIH caused by any reason including Riehl's melanosis. Lasers Surg. Med. © 2020 Wiley Periodicals LLC